2002
DOI: 10.1074/jbc.m206595200
|View full text |Cite
|
Sign up to set email alerts
|

Repression of DAX-1 and Induction of SF-1 Expression

Abstract: Angiotensin II (Ang II) and adrenocorticotropic hormone stimulate aldosterone biosynthesis in the zona glomerulosa of the adrenal cortex through induction of the expression of the steroidogenic acute regulatory (StAR) protein, which promotes intramitochondrial cholesterol transfer. To understand the mechanism of this induction of the StAR protein, we have examined the effect of Ang II and forskolin, a mimicker of adrenocorticotropic hormone action, on two transcription factors known to modulate StAR gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 51 publications
2
5
1
Order By: Relevance
“…These results are consistent with earlier reports [41][42][43]. Erik Willems et al suggested that FSK acted on the expression of SF-1 mRNA at the transcriptional level, and this was determined to be possible because FSK-induced enhanced expression of SF-1 mRNA was almost completely abolished by actinomycin D [39]. Furthermore, multiple SF-1 binding sites are present in the CYP11A1 promoter [44] and the StAR promoter [45].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with earlier reports [41][42][43]. Erik Willems et al suggested that FSK acted on the expression of SF-1 mRNA at the transcriptional level, and this was determined to be possible because FSK-induced enhanced expression of SF-1 mRNA was almost completely abolished by actinomycin D [39]. Furthermore, multiple SF-1 binding sites are present in the CYP11A1 promoter [44] and the StAR promoter [45].…”
Section: Discussionsupporting
confidence: 82%
“…FSK is a mimic of an adrenocorticotropic hormone mode of action. It has been previously reported that FSK dramatically increased SF-1 protein and mRNA levels by repressing DAX-1 protein and mRNA expression [39]. The clinical study also observed the role of FSK in significantly increasing lean muscle mass, bone mass, and testosterone in overweight and obese men [40].…”
Section: Discussionsupporting
confidence: 54%
“…Although the StAR gene lacks cAMP-responsible element (CRE) recognition sites in its promoter region (39), cAMP is one of the most potent activators of the StAR promoter, probably acting through CCAT/enhancer binding protein (C/EBP) response elements (39 -41). Induction of the StAR protein expression also directly correlates with inhibition of the dosage-sensitive sex reversal adrenal hypoplasia congenital critical region on the X-chromosome, gene 1 (DAX-1) and activation of steroidogenic factor 1 (SF-1) transcription factors (42). However, in our experiments, PKG II activated aldosterone release from ZG cells but, in contrast to PKA, did not stimulate StAR gene expression (Fig.…”
Section: Activation Of Pkg II In Zg Cells Increased Aldosterone Producontrasting
confidence: 46%
“…Likewise, several additional signaling pathways have also been demonstrated to play important roles in regulating StAR expression. These include calcium regulated transduction systems [59,[86][87][88][89][90], arachidonic acid metabolites [91,92], chloride ion channels [93,94], and mitogen activated protein Kinase (MAPK)/extracellular signal-related kinases (ERKs) [95,96].…”
Section: Regulation Of Star Expressionmentioning
confidence: 99%